Analysis of Stray Kids Brand Ambassadors on Purchase Decisions with Brand Awareness as a Mediating Variable - R. Viera Raina Firdiena; Kokom Komariah; Faizal Mulia Z (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the impact of Brand Ambassadors on purchasing decisions for Ultra Milk UHT milk products with Brand Awareness as a mediating variable. The focus of this study is Ultra Milk consumers in Sukabumi City using quantitative approach and descriptive-verification method. Data were obtained from 200 respondents selected through purposive sampling technique and analyzed using AMOS 29 software. The results of data processing show that brand ambassadors have a significant effect on brand awareness (C.R = 4.282 > 1.65 with p-value = 0.000 < 0.05). Furthermore, brand ambassadors have a significant effect on purchase decisions (C.R = 2.977> 1.65 with a p-value = 0.003 <0.05). Then, brand awareness has a significant effect on purchase decisions (C.R = 5.412 > 1.65 with a p-value = 0.000 < 0.05). In addition, brand awareness acts as an effective mediator in the relationship between brand ambassadors and purchase decisions (sobel test = 3.338> 1.65 with p-value= 0.000< 0.05). Thus, brand awareness is able to bridge the influence of brand ambassadors on purchase decisions among Ultra Milk consumers in Sukabumi City.